Plasmodium berghei-Mediated NRF2 Activation in Infected Hepatocytes Enhances Parasite Survival. (12th March 2022) - Bindschedler, Annina; Schmuckli-Maurer, Jacqueline; Wacker, Rahel; Kramer, Nicolas; Rehmann, Ruth; Caldelari, Reto; Heussler, Volker T.
Abstract : The protozoan parasite Plasmodium, causative agent of malaria, initially invades and develops in hepatocytes where it resides in a parasitophorous vacuole (PV). A single invaded parasite develops into thousands of daughter parasites. Survival of the host cell is crucial for successful completion of liver stage development. Nuclear factor erythroid-derived 2-related factor 2 (NRF2) is a transcription factor known to induce transcription of cytoprotective genes when activated. Here we show that NRF2 is activated in Plasmodium berghei -infected hepatocytes. We observed that this NRF2 activation depends on PV membrane resident p62 recruiting KEAP1, the negative regulator of NRF2. Disrupting the NRF2 gene results in reduced parasite survival, indicating that NRF2 signaling is an important event for parasite development in hepatocytes. Together, our observations uncovered a novel mechanism of how Plasmodium parasites ensure host cell survival during liver stage development.